2020
DOI: 10.21037/tp-20-219
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of a ketogenic diet for children with refractory epilepsy in China: a retrospective single-center cohort study

Abstract: Background: The ketogenic diet (KD) has been implemented in many different counties. However, in China, study concerning the efficacy of the KD is still at an early-stage of evaluation. Furthermore, the KD is thought to be incompatible with Chinese children because of its lack of palatability, especially for the Asian population. In addition, its substantial antiepileptic effect remains to be confirmed.Methods: To evaluate the efficacy and safety of the KD treatment of refractory childhood epilepsy in China, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
3
8
0
Order By: Relevance
“…The retention rate in previous study groups ranged from 20 to 80% at 6 months and from 10 to 60% at 12 months and was significantly related to overall clinical teamwork, the educational level of parents, and the efficacy of KD therapy. 8,9,[12][13][14] The data in our report were consistent with the literature, as 69.6 and 41.1% of patients maintained their special diet at 6 and 12 months in our cohort, respectively, and 23.2% still adhered to KD therapy one and a half years later. In our cohort, two common reasons for discontinuing trials were poor curative effects and adverse reactions.…”
Section: Discussionsupporting
confidence: 91%
“…The retention rate in previous study groups ranged from 20 to 80% at 6 months and from 10 to 60% at 12 months and was significantly related to overall clinical teamwork, the educational level of parents, and the efficacy of KD therapy. 8,9,[12][13][14] The data in our report were consistent with the literature, as 69.6 and 41.1% of patients maintained their special diet at 6 and 12 months in our cohort, respectively, and 23.2% still adhered to KD therapy one and a half years later. In our cohort, two common reasons for discontinuing trials were poor curative effects and adverse reactions.…”
Section: Discussionsupporting
confidence: 91%
“…Nausea/vomiting, diarrhea, and constipation are the most common gastrointestinal (GI) side effects of a VLCKD as we also found in our study [constipation (28%), vomiting/nausea (15.1%), diarrhoea (12.3%)] and as already have been reported in studies carried out in normal weight subjects [ 32 34 ]. In an RCT, 77 healthy participants were randomized to receive a VLCKD, a low-carbohydrate diet or a low-carbohydrate diet containing 5%, 15% and 25% total energy from carbohydrates, respectively, for 3 weeks [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Statistically significant increase in diarrhoea and constipation severity was observed in the VLCKD group [ 32 ]. In a prospective study of 147 children with refractory epilepsy conducted to evaluate the efficacy and safety of 6 months KD treatment, the second most common side effect of dietary treatment was diarrhoea [ 34 ]. In another similar study of 12 adults with refractory epilepsy treated with KD for 4 months, mild side effects included nausea/vomiting, constipation, and diarrhoea [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acidosis and other adverse events were reduced in our cohort, however we note that different studies showed various proportion of adverse events. In our patients the beta-hydroxybutyrate level was physiological or nutritional, only one patient occurred acidosis, which was comparable with Kang HC et al [43] and Li H et al [44]. However, Kim et al [35] found that the incidence of acidosis was 6% at 3 months; Lyczkowski DA et al [45] found that the proportion of metabolic acidosis was 39.4%.…”
Section: Discussionsupporting
confidence: 87%